Методы математической физики. Специальные функции. Основы комплексного анализа. Элементы вариационного исчисления и теории обобщенных функций рабочая тетрадь учебное пособие для вузов - Багров физик профессор Томского государственного университета; Белов; Задорожный математик доцент Томского политехнического университета, кандидат физико-математических наук; Трифонов российский физик, математик профессор Томского политехнического университета, доктор физико-математических наук (Изд-во ТПУ, 2012)
This textbook is devoted to the presentation of methods of the theory of functions of complex variable, foundations of calculus of variations, and theory of generalized functions. The body of the theoretical material contained in the textbook complies with the current program of the course of higher mathematics for physical engineering and physical specialities of universities. The theoretical course is supplemented with individual tasks (30 variants) on "Theory of Functions of Complex Variable" of the course "Higher mathematics and mathematical physics". The textbook can be useful to the graduate students, magisters, and postgraduates specializing in theoretical and mathematical physics. The textbook is intended for students and post-graduates of physical and engineering departments.